Value Contestation in Traditional Spaces: A Case Study of the Conflict in the Implementation of Gadeso in Pecalukan - Aisha Fadhila (GoAcademica Research & Publishing, 2023)
This research presents a comprehensive discussion of social conflict in the implementation of the gadeso tradition that occurs in the community in Pecalukan Subdistrict. The main points of discussion contained include conflict mapping, phasing and dynamics of conflict, as well as forms of conflict resolution efforts. This research uses a qualitative method with a case study approach. As a unit of analysis, this research uses the perspective of conflict theory by Ibnu Khaldun together with the concepts initiated by Geertz regarding santri and abangan. From the research that has been carried out, it can be seen that the root of the conflict comes from strong differences in values between social groups (ashabiyah) in Pecalukan Subdistrict. Namely, between the santri group and the abangan group who then contest each other and fight for power over the truth in the gadeso tradition, thus creating an attempt at domination and giving rise to conflict. This condition is further exacerbated by the stigma of